An Alternative Theory of Binocularity - Ng, Cherlyn J.; Purves, Dale (Frontiers in Computational Neuroscience, 2019)
The fact that seeing with two eyes is universal among vertebrates raises a problem that has long challenged vision scientists: how do animals with overlapping visual fields fuse non-identical right and left eye images to achieve cyclopean vision and the perception of depth that follows? Most theories address this problem in terms of matching corresponding images on the right and left retinas. Here we suggest an alternative theory of binocular vision based on anatomical correspondence that circumvents the correspondence problem and provides a rationale for ocular dominance.